2015
DOI: 10.1037/rmh0000015
|View full text |Cite
|
Sign up to set email alerts
|

An outcome study of Seeking Safety with rural community-based women.

Abstract: This pilot study investigated the impact of Seeking Safety (SS) on rural women with comorbid substance abuse and trauma problems. SS is an evidence-based, presentfocused therapy that provides coping skills and psychoeducation. Despite its demonstrated effectiveness, this is the first known study using SS with rural women. Investigating the efficacy of evidence-based treatments with rural populations is especially important because, compared with urban residents, they are more likely to meet criteria for comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Some of the findings in this study were consistent with other rural studies (e.g., Hill, Cantrell, Edwards, & Dalton, 2016;Keefe & Curtain, 2012;Patitz et al, 2015;Zhang et al, 2008), whereas other findings were previously unreported. Participants were willing to acknowledge and take responsibility for their roles that necessitated the utilization of mental health services (e.g., addiction relapse and the nonadherence to psychotropic medication).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Some of the findings in this study were consistent with other rural studies (e.g., Hill, Cantrell, Edwards, & Dalton, 2016;Keefe & Curtain, 2012;Patitz et al, 2015;Zhang et al, 2008), whereas other findings were previously unreported. Participants were willing to acknowledge and take responsibility for their roles that necessitated the utilization of mental health services (e.g., addiction relapse and the nonadherence to psychotropic medication).…”
Section: Discussionsupporting
confidence: 92%
“…The provision of mental health services in rural communities has been characterized by a shortage of mental health professionals, which has been associated with professional isolation, job dissatisfaction, burnout, and fewer peer collaboration opportunities and referral options (Hendryx, 2008;Rishel & Hartnett, 2015). From the rural client perspective, stigma, concerns about anonymity, financial constraints, and the lack of transportation affect utilization of mental health services (Gonzalez & Brossart, 2015;Patitz, Anderson, & Najavits, 2015;Reed, Messler, Coombs, & Quevillon, 2014).…”
mentioning
confidence: 99%
“…It seems necessary to develop detailed tracking of each abused, addicted woman's progress to prevent her from becoming an early treatment dropout. Knowing the specific characteristics of abused women will allow therapists to implement individually tailored strategies to increase retention in intervention programs and to provide better treatment outcomes, in the same way as Seeking Safety programs with PTSD and addiction (Patitz et al, 2015;Searcy & Lipps, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown greater consumption at the beginning of treatment (Clark, Masson, Delucchi, Hall, & Sees, 2001) and higher rates of relapse during treatment (Farley, Golding, Young, Mulligan, & Minkoff, 2004) among patients who present lifelong histories of abuse. Although some programs have been developed with women with posttraumatic stress disorder (PTSD) and addiction in an integrated manner (Patitz, Anderson, & Najavits, 2015;Searcy & Lipps, 2012), little is known about the specific clinical characteristics and the therapeutic progression of addicted women with histories of abuse in a general addiction treatment program.…”
Section: Introductionmentioning
confidence: 99%
“…The final article is a brief report by Patitz, Anderson, and Najavits (2015), entitled "An Outcome Study of Seeking Safety With Rural Community-Based Women." I have heard of Seeking Safety (http://www.seekingsafety.org) for many years, but only recently was able to attend a presentation by its developer, Dr. Lisa M. Najavits.…”
Section: The Current Issuementioning
confidence: 99%